Main genetic diseases in dogs of the Border Collie breed: a review (Research, Society and Development, 2022)
The Border Collie breed is very popular in Brazil and has certain susceptibilities to express genetic diseases, with different manifestations. This review analyzes the main genetic diseases in Border Collie dogs and that can also affect other herding breeds. The research was carried out through a bibliographic survey and aims to demonstrate specifications of each disease, comparing their incidences in Brazil and other countries, as well as raising awareness among veterinarians and guardians about the presence and possible reproduction of these diseases when not studied. It can be concluded that the rarity of genetic diseases in the Border Collie breed is relative and results more from the lack of knowledge of guardians and veterinarians than from their low prevalence. Control must be carried out through genetic markers and imaging tests, in addition to planning the cross breeding of dogs to avoid homozygosity.